PENGEMBANGAN LKPD MENULIS PUISI MENGGUNAKAN PENDEKATAN SAINTIFIK BERBASIS OUTDOOR CLASS - Helda Susanti; Abdul Muktadir; Bambang Parmadi (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to (1) describe the development of student workseet using a scientific approach based on outdoor class poetry writing materials at SD Negeri 66 Seluma and SD Negeri 104 Seluma, (2) determine the feasibility of LKPD using a scientific approach based on outdoor class poetry writing materials at SD Negeri 66 Seluma and SD Negeri 104 Seluma, (3) to determine the feasibility of LKPD using a scientific approach, SD Negeri 66 Seluma and SD Negeri 104 Seluma. This research is a development research. The method used is ADDIE by adapting 5 development steps, namely (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. LKPD produced in this study is in accordance with the needs of students and teachers. The subjects in this study were fourth grade students at SD Negeri 66 Seluma and SD Negeri 104 Seluma. The instruments used were questionnaires and interview guidelines for needs analysis, expert validation sheets to test LKPD validation and teacher and student response questionnaires to test the practicality of LKPD. The results showed that the LKPD developed was valid and feasible to use. This is shown from the analysis of the percentage of expert validation results that are in the "valid" criteria. From the results of the analysis of the coefficient of Aiken V is in the "feasible" criteria. LKPD developed is very practical to be used by teachers and students in learning. This is indicated by the results of the teacher's response analysis being in the "Very practical" criteria. From the analysis of student responses, they are in the "practical" criteria.